Deuterium Exchange of the α-Methylene Group Protons in the Quinazolones. III. Environment Influence on the Exchange Rate (Journal of Basic and Applied Research in Biomedicine, 2022)
By 1H NMR spectroscopy methods the exchange process of α-methylene group protons of deoxyvasicinone by deuterium atoms in the medium of CD3OD+NaOH and CD3OD+CD3COOD depending on NaOH concentration and temperature of the solution and CD3COOD have been investigated. It was shown that NaOH and CD3COOD have exchange initiator character, and their effect on the concentration are linear to D-exchange rate. The exponential dependence on temperature allowed us to determine the potential barrier of the initiation of the D- exchange process for deoxyvasicinone in the CD3COOD.